An observational study to compare adenosine deaminase level among diabetes patients - Sharma, Vivek; Bhattacharya, Sangeeta; Sarkar, Poornima Dey; Garima, Gini; Gour, Neeraj; Chaudhary, Meenakshi (International Journal of Research in Medical Sciences, 2019)
Background: Obesity is a complex disorder that involves some degree of over-consumption1 coupled with a metabolic derangement. As ADA has been putatively associated with inflammation, and adipose tissue inflammation is the hallmark of insulin resistance in obese T2DM patients. This study attempted to compare serum ADA in T2DM subjects. Methods: This observational cross-sectional study was conducted in the Department of Biochemistry at MGM Medical College and MY Hospital. All the patients and controls were clinically examined, and routine biochemical tests were analyzed for all subjects. ANOVA has been applied to assess the variance between groups. Results: Mean age of controls was 56.91 years where as mean age in the group of a subject with Obesity with diabetes was 40.91 years and with Obesity without diabetes was 48.10 years. ADA level was more among diabetes patients having obesity than diabetes patients having no obesity and controls. Conclusions: This is very much evident through this study that ADA may be treated as prognostic predictor of diabetes either linked to obesity or not, though more studies are warranted in same direction to make this finding conclusive and acceptable biochemical evidence.